Upaya Peningkatan Literasi Berbahasa Inggris Siswa SDN 001 Lipat Kain Selatan (STMIK Dharmapala Riau, 2024)
Currently, the younger generation is required to be able to keep up with world changes, one of which is language. English as an international language is used almost all over the world in every activity. Therefore, the existence of English subjects in schools is an effort to make students able to have English language skills. To make learning English more interesting, a new learning strategy was created, namely English Play. English Play as a form of a new method of learning English for students, especially elementary schools, aims to foster interest in and improve students’ ability English languange. English Play is designed to make learning English is fun for the students. This activity was carried out at SDN 001 Lipat Kain Selatan as one of the integrated schools in Lipat Kain Selatan. English Play got a good response from the students because it made them excited to learn English. Implementation of English play at SDN 001 Lipat Kain Selatan as a form of community service by students Kukerta of Riau University